The Association of Dietary Intakes and Gut Microbiota in Korean Lean and Obese Patients with Type 2 Diabetes - Choi, Ha-Neul (Curr Dev Nutr, 2020)
OBJECTIVES: Several studies have reported that dysbiosis of the gut microbiota as a key role in rapid progression of insulin resistance and type 2 diabetes mellitus (T2DM). The diet can affect the composition and proper function of the gut microbiota. However, the association of diets, blood parameters, and gut microbiota studies have not been fully investigated in Korean subjects. Thus, the aim of this study was to characterize and compare the dietary intake, blood parameters, and gut microbiota in Korean lean and obese T2DM patients. METHODS: T2DM patients were recruited. We are classified as obese group (ODM; body mass index (BMI) ≥ 25 kg/m(2)) and lean group (LDM; BMI < 25 kg/m(2)). The anthropometric data, body composition, and blood parameters were measured. 3-day food record evaluation was used to analyze dietary intake using computer aided nutritional program (version. 5.0). The gut microbiota was investigated by quantitative real-time PCR. The collected data were analyzed statistically using SPSS statistics (version 25.0). RESULTS: Body weight, body fat mass, and % body fat of the ODM group were significantly higher than the LDM group. Compared with the ODM group, serum adropin and adiponectin of the LDM group were significant higher, whereas serum leptin of the LDM group was significant lower. The intakes of energy, fat, cholesterol, and protein in the ODM group tended to be higher in comparison the LDM group, although the difference was not significant. The difference of gut microbiota between the LDM and ODM groups was not found. However, the Firmicutes/Bacteroidetes ratio was significantly increased in accordance with BMI, the Prevotella was also positive correlated with PUFA intake. In ODM group, the consumption of vegetables was positively correlated with the Lactobacillus. CONCLUSIONS: We found that the diet can affect the composition of gut microbiota and the effects of diet were different depending of the body weight in Korean T2DM patients. FUNDING SOURCES: This work was supported by the National Research Foundation of Korea (NRF) grant funded by the Korean government (MSIP).